Heavy metals in water and sediment of Way Ratai River due to small-scale gold mining activities in Pesawaran Regency, Lampung Province (Part I: mercury, cyanide, lead, and arsenic) - Istighfarah, Vedelya; Dermiyati, Dermiyati; Rinawati; Prasetia, Hendra; Fasya, Muhammad Rizki Firdaus (Journal of Degraded and Mining Lands Management, 2025)
The use of mercury and cyanide in the gold separation process at small-scale gold mining in Pesawaran Regency can carry mercury (Hg), cyanide (CN-), lead (Pb), and arsenic (As) as other heavy metals that are also harmful to the environment. This study aimed to determine the concentration and distribution of some heavy metals (Hg, CN-, Pb, As) found in the water and sediment of the Way Ratai River. Water and sediment samples were taken at 5 points along the Way Ratai River. The heavy metal analysis method used a Mercury Analyzer, Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES), Atomic Absorption Spectrophotometry, and X-ray fluorescence. Mapping the distribution of heavy metal concentrations uses ArcGIS with the Inverse Distance Weighting (IDW) method. The results showed that the average concentration of Hg in water was 0.006 ppm, As was 0.023 ppm, and CN- was 0.003 ppm; Pb was not detected in river water. Meanwhile, in the river sediments, the average Hg was 11.83 ppm, As was 449.10 ppm, Pb was 450.88 ppm, and CN- was 0.38 ppm. It can be concluded that the concentration of heavy metals in the sediment of Way Ratai River is in the high category; the heavy metal content in river sediment is higher than that in water. For this reason, it is necessary to manage waste from gold processing activities, such as coagulation and absorption, to reduce the potential for environmental pollution.